2020
DOI: 10.3389/fgene.2020.489357
|View full text |Cite
|
Sign up to set email alerts
|

Cascabel: A Scalable and Versatile Amplicon Sequence Data Analysis Pipeline Delivering Reproducible and Documented Results

Abstract: Marker gene sequencing of the rRNA operon (16S, 18S, ITS) or cytochrome c oxidase I (CO1) is a popular means to assess microbial communities of the environment, microbiomes associated with plants and animals, as well as communities of multicellular organisms via environmental DNA sequencing. Since this technique is based on sequencing a single gene, or even only parts of a single gene rather than the entire genome, the number of reads needed per sample to assess the microbial community structure is lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…The raw data were processed using the NIOZ in-house amplicon sequence analysis pipeline “Cascabel” ( Abdala Asbun et al, 2020 ), according to the following specifications. First, quality on the reads was assessed with FastQC 1 , then paired-end reads were merged with PEAR v0.9.10 ( Zhang et al, 2014 ) with a p value set to 0.05 (for the statistical test of a possible assembly) and a minimum overlap of 10 bases.…”
Section: Methodsmentioning
confidence: 99%
“…The raw data were processed using the NIOZ in-house amplicon sequence analysis pipeline “Cascabel” ( Abdala Asbun et al, 2020 ), according to the following specifications. First, quality on the reads was assessed with FastQC 1 , then paired-end reads were merged with PEAR v0.9.10 ( Zhang et al, 2014 ) with a p value set to 0.05 (for the statistical test of a possible assembly) and a minimum overlap of 10 bases.…”
Section: Methodsmentioning
confidence: 99%
“…The prokaryotic 16S rRNA gene amplicon sequences were analyzed using the Cascabel data analysis pipeline (Abdala Asbun et al, 2020). Raw forward and reverse reads were merged using PEAR (Zhang et al, 2014).…”
Section: Dna Extraction and Phylogenetic Analysismentioning
confidence: 99%
“…Longer-chain fatty acids and branched fatty acids like MAs have been shown to be more resistant than other biomolecules (e.g., short-chain fatty acids) to diagenetic changes in diverse studies of fossil forests, sediment cores from the Gulf of California and petroleum systems (Staccioli et al, 2002;Wenger et al, 2002;Camacho-Ibar et al, 2003). Under the right conditions, fatty acids may be preserved as bound compounds in ancient sediments through the Miocene (Ahmed et al, 2001). Indeed, studies have indicated the presence of MAs of M. tuberculosis on ancient bones from a 17 000-year-old bison and from a ca.…”
Section: Role Of the Mycobacteria At The Censo Seepmentioning
confidence: 99%